10g-5=5(1-2g)

Simple and best practice solution for 10g-5=5(1-2g) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10g-5=5(1-2g) equation:


Simplifying
10g + -5 = 5(1 + -2g)

Reorder the terms:
-5 + 10g = 5(1 + -2g)
-5 + 10g = (1 * 5 + -2g * 5)
-5 + 10g = (5 + -10g)

Solving
-5 + 10g = 5 + -10g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '10g' to each side of the equation.
-5 + 10g + 10g = 5 + -10g + 10g

Combine like terms: 10g + 10g = 20g
-5 + 20g = 5 + -10g + 10g

Combine like terms: -10g + 10g = 0
-5 + 20g = 5 + 0
-5 + 20g = 5

Add '5' to each side of the equation.
-5 + 5 + 20g = 5 + 5

Combine like terms: -5 + 5 = 0
0 + 20g = 5 + 5
20g = 5 + 5

Combine like terms: 5 + 5 = 10
20g = 10

Divide each side by '20'.
g = 0.5

Simplifying
g = 0.5

See similar equations:

| 7x-7=21+3x | | 5k+7=5(k+1) | | 6x^2+49x+21=0 | | -2(7x+45)=-4(x+25) | | 8(x-4)=72 | | 9n-24-6n=3n+48+8n | | 1-3x+2x=0 | | 3x^2-11=20 | | if(2x+1)(x-5)=2(x^2-1) | | 8(x+2)/3=3x+8 | | 6x+30=12x-36 | | ((3x)/(6pi))+((1-x)/3)=0 | | ((3x)/(6pi))+((1-x)/3) | | 24x+(3x+200)=107100 | | 2(x+1)=8+x | | 13-x=9x+8 | | b^2-12b+48=0 | | 9x-26=1 | | 7x+16=3m | | 7x-16=3m | | (x+5)(x+6)=130 | | 5/6x4/9 | | 5+0.5x=200 | | 2(4-x)=x-(5x+8) | | 6(2n+3)=28+7n | | ((3*6)-5+(2*6)+8)/(2*6) | | (3w-5+2w+8)/2w | | -15=14m+5 | | y/6+9=17 | | 8f-7=65 | | 3x+2x=170 | | 3x=170 |

Equations solver categories